Analisis Break Even Point Budidaya Bunga Potong Krisan Di Kelurahan Kakaskasen 1 Kota Tomohon (Studi Kasus Kelompok Tani KIBERTA) - Boyke Jansen Gosal; Noortje M. Benu; Celcius ., Talumingan (Sam Ratulangi University, 2016)
The objective of this research is to calculate the Break Even Point (BEP), which is an approach to analyze production volume planning and increasing business prospect. This research was carried out from June to July 2016. Data used in this research was primary data that obtained from interview and secondary data obtained from related agencies and journals to support this research. Data analysis used Break Even Point analysis, which is to analyze the business’s break even point in both rupiah and unit. KIBERTA farmer group has a directly Marketing channel with the buyers that directly come to KIBERTA’s greenhouse. Chrysanthemum stalk flower cultivation in this farmers carried out in one greenhouse per period in turns, by order with 6 weeks gap in planting between greenhouses and farmers harvesting once in three weeks with four total of greenhouses which is in size 10 x 25 m2, 20 x 25 m2, 8 x 14 m2, and 8 x 15 m2. This farmers sell Rp. 3000, - per stalk in all type and colors. The research result shows that from 100% which is planted only 70% were able to be harvest / within selling requirement and based on analysis results from table and graphs found out that KIBERTA farmers’ chrysanthemum stalk flower cultivation from revenue (Rupiah) and production (unit), exceed the Break Even Point and able to gain profits in all greenhouses *jnkd*.